Proposed Solutions for the Main Challenges and Security Issues in IoT Smart Home Technology - Ahmed Abdulfatah Abdlrazaq; Sapan Noori Azzez; Mardin Abdulla Anwer; Shaho Ismael Hassen (Zanco Journal of Pure and Applied Sciences, 2023)
The IoT has become a trend in recent years, and the smart home system has achieved great interest due to its need and requirement from consumers around the world. Smart home technology refers to the devices that are connected over the internet to monitor, support, and control the home in order to make our life easier. The revolution in technology has made homes more convenient, efficient, and even simpler. However, there are some challenges and obstacles that need to take into consideration when using a smart home system. Based on a comprehensive survey, this study aims to provide an overview of the critical security issues for IoT smart home systems and propose potential solutions to mitigate these risks by understanding vulnerabilities and applying security measures to ensure that the IoT system is more reliable and safe. The challenges and security issues highlighted with an emphasis on providing solutions, as well as smart home approaches and IoT layers.